Help with a proof: Normal subgroup

Hi.

I need to prove:

$\displaystyle H\triangleleft G \Leftrightarrow \forall g\in G,\hspace{5} \forall h\in H:\hspace{5} g^{-1}hg\in H$

So, one direction is quite easy:

$\displaystyle \Rightarrow$ :

If $\displaystyle H$ is a subgroup of $\displaystyle G$, it follows that $\displaystyle \forall g\in G$: $\displaystyle gH=Hg$.

in particular, for every $\displaystyle h\in H$, $\displaystyle gh=hg$ , so $\displaystyle h=g^{-1}hg$, $\displaystyle \forall g\in G, \forall h\in H$.

but the second direction is not quite clear for me:

$\displaystyle \Leftarrow$ :

Since $\displaystyle \forall g\in G$, $\displaystyle \forall h\in H$: $\displaystyle g^{-1}hg\in H$, there exist some $\displaystyle h_0\in H$, such that $\displaystyle g^{-1}hg=h_0$

and then:

$\displaystyle gh_0=hg$

but how do I know that $\displaystyle h_0=h$?

Thanks in advance.

Re: Help with a proof: Normal subgroup

Quote:

Originally Posted by

**Stormey** $\displaystyle H\triangleleft G \Leftrightarrow \forall g\in G,\hspace{5} \forall h\in H:\hspace{5} g^{-1}hg\in H$

So, one direction is quite easy:

$\displaystyle \Rightarrow$ :

If $\displaystyle H$ is a subgroup of $\displaystyle G$, it follows that $\displaystyle \forall g\in G$: $\displaystyle gH=Hg$.

You mean, if H is a *normal* subgroup.

Quote:

Originally Posted by

**Stormey** in particular, for every $\displaystyle h\in H$, $\displaystyle gh=hg$

$\displaystyle gH=Hg$ does not mean this. It means that sets gH and Hg are equal. Now, gH = {gh | h ∈ H} and Hg = {h'g | h' ∈ H}. For an arbitrary h ∈ H, the fact that gh ∈ {h'g | h' ∈ H} means that there exists some h' ∈ H such that gh = h'g. Similarly, for every h' ∈ H there exists an h such that gh = h'g.

Re: Help with a proof: Normal subgroup

Hi, emakarov.

thanks for the help.

Quote:

Originally Posted by

**emakarov** You mean, if H is a *normal* subgroup.

Yes, sorry. I meant normal.

Quote:

Originally Posted by

**emakarov** $\displaystyle gH=Hg$ does not mean this. It means that sets gH and Hg are equal. Now, gH = {gh | h ∈ H} and Hg = {h'g | h' ∈ H}. For an arbitrary h ∈ H, the fact that gh ∈ {h'g | h' ∈ H} means that there exists some h' ∈ H such that gh = h'g. Similarly, for every h' ∈ H there exists an h such that gh = h'g.

OK, I get now why it's wrong to say that $\displaystyle gH=Hg$ means gh=hg, so then how do I go from "there exists an h such that gh = h'g" to gh=hg for every g in G, and for every h in H?

**edit

scrap that last post.

I got it.

for some reason I thought that every normal subgroup is abelian...

Re: Help with a proof: Normal subgroup

Quote:

Originally Posted by

**Stormey** how do I go from "there exists an h such that gh = h'g" to gh=hg for every g in G, and for every h in H?

You don't because gH = Hg does not imply gh = hg for every h ∈ H and g ∈ G. But gh = hg is not required for the proof you need.

Re: Help with a proof: Normal subgroup

Thanks.

edited my last post.